Novas escavações na Mamoa 1 de Chã de Parada- Baião, Serra da Aboboreira, 1990 - Jorge, Vitor Oliveira; Pereira, Antonio da Silva; Nunes, Carla Stockier; Varela, Jose Manuel (Trabalhos de Antropologia e Etnologia, 2021)
.